ANALYSIS OF FUEL QUALITY EFFECT ON THE LIFE TIME FROM HIGH-PRESSURE PUMP OF ENGINE MTU 12 V 4000 M 71 - Sutrisno Sutrisno; Wawan Kusdiana; Anton Nugroho; Abdul Rahman (JOURNAL ASRO, 2020)
Fuel is one of the important components in the combustion process. A good fuel is a clean fuel where the fuel is colorless, watery, has a high flash point, it can ignite spontaneously at a temperature of 350ºC, and has a specific gravity of about 0.82-0.86. On the other hand, KRI Kelabang-826 is an Indonesian republic warship that functions as a patrol boat. This causes the ship to have a medium duty engine, the MTU 12 V 4000 M 71 engine. This engine itself is a sophisticated engine because it uses common rail technology with a High-Pressure Pump as the supplying pump. This pump is very susceptible to damage, this is proven by not achieving the life time of the High-Pressure Pump which is 7500 Running Hours or once a W5- level maintenance. This is caused by poor quality of fuel, where the fuel used contains water and impurities. Therefore, the preventive ways are needed in order to achieve the life time of this High-Pressure Pump component. Keywords: Fuel Quality, MTU 12 V 4000 M 71, High-Pressure Pump, and Condor Class.